The Immigration Law 1.094 of 1975 as a Discursive Device in the Context of the Civil- Military Dictatorship - Brower-Beltramin, J; Contreras-Candia, L (UNIV SANTIAGO CHILE, FAC TECNOLOGICA, 2022)
In our times, migration has become a priority issue on the international agenda. The need to have appropriate legislation on this matter is unavoidable, ensuring protection for those who move, seeking a better quality of life. In this work, we analyze the immigration law 1,094 promulgated by the Chilean civic-military dictatorship in 1975. Considering its discursive/legal status, we are interested in its analysis as a legal reference in relation to subsequent projects and the current Immigration Law, in force since the year 2021. For its reading, analysis and understanding, we have resorted to the concept of knowledge/power device, developed by Foucault, particularly in its discursive dimension. This allows us to characterize the semantic and ideological construction that is made of migrant subjects, in the context of a dictatorship, regulated by conditions of normative of a totalitarian